Profil Sel Natural Killer (NK) dalam Darah Perifer dan Jaringan Tumor Penderita Lesi Prakanker dan Karsinoma Sel Skuamosa Serviks - SARASWATI, WITA (Indonesian Journal of Cancer, 2014)
This research was performed to investigate the profile of Natural Killer (NK) cells in peripheral blood and tumor tissues of cervical pre cancerous lesion and squamous cell carcinoma of cervix patients. This research was an observational analysis study with cross-sectional design of 47 subjects which comprises of 17 cervical pre cancerous lesion patients, 8 early stage squamous cell carcinoma of cervix patients and 22 late stage squamous cell carcinoma of cervix patients in Dr. Soetomo Hospital-Airlangga University teaching hospital, Surabaya. After clinical and histopatologic diagnosis was established, NK cell count was perfomed on the biopsies, and both NK cell count and percentage of activated NK cells was performed on the peripheral blood of those three groups. From this research, it was found that the average number and percentage of activated NK cells within peripheral blood of cervical pre cancerous lesion patients were lower (349.65 cell/Î¼L; 15.13%) compared with early stage carcinoma (552 cell/Î¼L; 18,40%) and late stage carcinoma (590.32 sel/Î¼L; 23.29%). NK cell expression of cervical tumor tissues on three groups are very low, 0.29% on cervical pre cancerous lesion patients; 0.45% on early stage cervical cancer patients; and 0.04% on late stage cervical cancer patients. Significant differences was found in the number of NK cells (p=0.016) and percentage of activated NK cells (p=0.041) within peripheral blood between pre cancerous lesion patients and late stage squamous cell cervical cancer patients, no significant difference was found in the number of NK cells within tumor tissue (p=0.278).